2016
DOI: 10.5966/sctm.2015-0341
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Mesenchymal Cells Improve Passive Immune Protection Against Lethal Venezuelan Equine Encephalitis Virus Exposure

Abstract: Direct injection of monoclonal antibodies (mAbs) is an important strategy to immediately protect the recipient from a pathogen. This strategy is critical during natural outbreaks or after the intentional release of bio-weapons. Vaccines require weeks to become effective, which is not practical for first responders immediately deployed to an infected region. However, mAb recipients often require booster shots to maintain protection, which is expensive and impractical once the first responders have been deployed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…However, numerous studies have consistently demonstrated that IV-infused cells largely become trapped in the capillaries of the lungs, where they fail to survive longer than a few days [15,29,[31][32][33][34][35].This phenomenon reduces the potential therapeutic bene t of the administered MSCs, a limitation cited in both clinical trials and animal studies [27,36,37]. In contrast, studies recently reported that engineered MSCs administered by IM were still detectable at the implant site >100 days after transplantation, and they continued to secrete a functional antibody into circulation [38]. Thus, in the present study, three routes of HUC-MSC transplantation in db/db mice were compared.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous studies have consistently demonstrated that IV-infused cells largely become trapped in the capillaries of the lungs, where they fail to survive longer than a few days [15,29,[31][32][33][34][35].This phenomenon reduces the potential therapeutic bene t of the administered MSCs, a limitation cited in both clinical trials and animal studies [27,36,37]. In contrast, studies recently reported that engineered MSCs administered by IM were still detectable at the implant site >100 days after transplantation, and they continued to secrete a functional antibody into circulation [38]. Thus, in the present study, three routes of HUC-MSC transplantation in db/db mice were compared.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon reduces the potential therapeutic benefit of the administered MSCs, a limitation cited in both clinical trials and animal studies [33,42,43]. In contrast, studies recently reported that engineered MSCs administered by IM were still detectable at the implant site > 100 days after transplantation, and they continued to secrete a functional antibody into circulation [44]. Thus, in the present study, three routes of HUC-MSC transplantation in db/db mice were compared.…”
Section: Discussionmentioning
confidence: 90%
“…This phenomenon prompted us that MSC transfusion by IV limited the potential therapeutic benefit in both clinical trials and animal studies [ 27 , 36 , 37 ]. However, engineered MSC transplantation by IM can live last for more than 100 days, and they perform their function by secreting a functional antibody into circulation [ 38 ]. Thus, in the present study, three routes of HUC-MSC transplantation in db/db mice were compared.…”
Section: Discussionmentioning
confidence: 99%